Blindness caused by idiopathic intracranial hypertension in the course of the obesity-hypoventilation syndrome – case report - Brzecka, Anna; Ejma, Maria; Gurański, Konstanty; Czak, Wojciech; Misiuk-Hojło, Marta (Klinika Oczna / Acta Ophthalmologica Polonica, 2023)
A woman with morbid obesity with severe form of the obesity hypoventilation (OH) syndrome with multiple obstructive sleep apneas (OSA) and hypopneas resulting in extremely low and long-lasting nocturnal arterial oxygen desaturations presented with developing over few weeks blindness. Increases of cerebrospinal fluid pressure during sleep along with obstructive sleep apneas were observed. Idiopathic intracranial hypertension (IIH) with papilloedema was diagnosed. Noninvasive ventilation was ineffective in reversing the consequences of papilloedema despite of reversion of sleep breathing disturbances. The impaired glymphatic system functioning was hypothesized as one of the factors asso-ciated with IIH development. Sleep disordered breathing should be searched in obese patients with suddenly developing blurred vision.